Association between the point-rating system used for oral health and the prevalence of Gram-negative bacilli in hematological inpatients: A retrospective cohort study. Issue 22 (4th June 2021) - Yoshizawa, Kunio; Moroi, Akinori; Iguchi, Ran; Yokomichi, Hiroshi; Ogihara, Shinji; Watanabe, Kazuaki; Nakajima, Kei; Kirito, Keita; Ueki, Koichiro
Abstract : Abstract: Gram-negative bacteremia is a major cause of death among hematology inpatients who require heavy-dose chemotherapy and hematopoietic stem cell transplantation. Gram-negative bacillus (GNB) is more likely to be detected when the oral health is poor. However, there is a dearth of studies on the relationship between oral assessment and prevalence of GNB in hematology inpatients. This retrospective study aimed to evaluate the relationship between the original point-rating system for oral health examinations (point-oral exam) and the prevalence of GNB in hematology inpatients at the hematology ward of the Yamanashi University Hospital. GNB was detected by cultivating samples from the sputum and blood of each patient. A total of 129 subjects underwent a medical checkup and point-oral exam. The sputum and blood culture results of 55 patients were included in this study. The total points of patients positive for GNB (n = 25, 45.5%) were significantly higher than those who were negative for GNB (total score: median, 25th, 75th, percentile; 6 [4, 7] vs 2 [1, 4]; P  = .00016). Based on the receiver operating characteristic analysis, a cutoff score of 5 proved to be most useful to detect GNB. An oral evaluation with a cutoff value of 5 or higher in the point-oral exam might indicate the need for a more thorough oral management to prevent the development of systemic infections from GNB.